The Correlation Between the Use of YouTube and Students' Motivation in Learning English Listening Skills - Kholida Ziya; Abdul Syahid; Zaitun Qamariah (International Journal Labs, 2025)
In the era of digital learning, YouTube has emerged as a platform that is not only for entertainment but also effective in language learning, particularly in improving English listening skills for EFL learners. Listening is a fundamental skill in language acquisition; however, many students face difficulties due to different accents, fast speech, and unfamiliar vocabulary. YouTube provides authentic audiovisual content that supports comprehension, captures students' interest, and enhances learning motivation. The purpose of this research was to identify the correlation between YouTube use and students' motivation to learn English listening skills at a university in Central Kalimantan, Indonesia. Using a quantitative correlational research design, 23 students participated as respondents and were assessed through a Likert-scale questionnaire measuring YouTube usage frequency and motivation levels. Data analyzed with Spearman's rank correlation indicated a significant positive relationship (rho = 0.502; p = 0.015), suggesting that higher YouTube usage is associated with higher students' learning motivation. The findings indicate that integrating YouTube into language learning provides authentic, engaging, and diverse materials that can enhance students' motivation and listening comprehension. However, motivation is also influenced by other factors such as classroom environment, teacher support, and social interactions. Future research is recommended to involve a larger sample and consider additional variables to better understand factors affecting learning motivation in digital contexts.